Physical preparedness and functional status of young players in the competition period - Svystun, Yu. D.; Trach, V. M.; Chornobaj, I. M.; Shavel, Kh. E. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose: evaluate physical preparedness and functional status of young players in the competitive period.